(untitled) (Ustozlar uchun, 2026)
This article explores the multifaceted advantages of Islam in influencing the behavior and development of children. It discusses how Islamic teachings and practices provide moral guidance, discipline, a sense of identity, empathy, cognitive development, conflict resolution skills, respect for diversity, financial literacy, physical well-being, and community engagement. By integrating these dimensions, Islam offers a comprehensive framework for nurturing the holistic well-being of young individuals and equipping them with the values and virtues needed to navigate life’s challenges and contribute positively to society.